The problem of quality of electric power functioning of ship electric power systems - D. Yu. Rudi (Омский научный вестник)
The article describes the problems of the quality of electric power functioning of ship electric power systems. The urgency of this problem is given. The importance of this problem increased directly together with the development of water transport. The objects of the technical fleet of marine power systems are particularly susceptible to the effect of conductive electromagnetic interference. Comparative analysis, given in the article, on the indicators of the quality of electricity of various standards has shown the existence of differences in requirements, which leads to downtime in work, the violation of the scientific and technical process, the marriage of products. The issue of solving the scientific and technical problem for improving the quality of electric power functioning of ship electric power systems is still not solved, which causes certain difficulties in finding the problem in a timely manner.